(untitled) (American Journal of Pedagogical and Educational Research, 2023)
In the manufacture of removable dentures, there is often a problem of design features, the choice of fixation method. Fixation systems with wire clasps are outdated, but outdated, but widely used in clinical practice. In addition to the fact that such prostheses are unaesthetic, they are not only unaesthetic, but also increase the atrophy of the tissues of the base of the prosthesis, which ultimately leads to a deterioration in the fixation of the prosthesis, which leads to a deterioration in the fixation of the prosthesis (Kalinina N.V., Markov B.P.). At present, a number of improved designs of prostheses have been proposed.A number of more advanced orthopedic structures have been proposed, allowing the use of the remaining teeth as supports for removable dentures (Kalinina N.V., Markov B.P.). As abutments for fixing removable dentures. One of these designs is a removable prosthesis with a telescopic fixation system.The telescopic fixation system is represented by a metal crown with a 6° cone in the fixed part. The removable part with a 6° cone is a plastic base on which an artificial tooth is attached.